Knowledge mobilization with and for equity-deserving communities invested in research: A scoping review protocol - Ramy Barhouche; Samson Tse; Fiona Inglis; Debbie Chaves; Erin Allison; Tina Colaco; Melody E. Morton Ninomiya (PLoS ONE, 2025)
The practice of putting research into action is known by various names, depending on disciplinary norms. Knowledge mobilization, translation, and transfer (collectively referred to as K*) are three common terminologies used in research literature. Knowledge-to-action opportunities and gaps in academic research often remain obscure to non-academic community partners and researchers in communities, policy and decision makers, and practitioners who could benefit from up-to-date information on health and wellbeing. Academic research training, funding, and performance metrics rarely prioritize or address non-academic community needs from research. We propose to conduct a scoping review on reported K* in community-driven research contexts, examining the governance, processes, methods, and benefits of K*, and mapping who, what, where, and when K* terminology is used. This protocol paper outlines our approach to gathering, screening, analyzing, and reporting on available published literature from four databases.